Mutual funds : an introduction to the core concepts - Mobius, Mark. (Chichester : Wiley, 2007)
"Students, investors and entrants to the business will find Mutual Funds: An Introduction to be a lively, practical and highly informative overview of one of the world's most important financial products. One could not ask for a better guide to the world of mutual funds than Mark Mobius, truly a legendary figure in global asset management
An introduction to mutual funds -- Types of mutual funds -- Making sense of mutual fund documents -- Analyzing performance -- Mutual fund costs -- Buying and selling mutual fund shares -- Building mutual fund portfolios -- The mutual fund industry : trends and growth drivers.
Includes bibliographical references and index.
Keywords: Mutual funds